Determinan Academic Dishonesty Behaviour Mahasiswa Akuntansi Dalam Online Exams: Perspektif Fraud Pentagon Dan Test Anxiety - Putri Nuril Wulanatining Asih; Sunaryanto Sunaryanto (Universitas Muhammadiyah Malang, 2022)
Academic dishonesty is one of global problems in the scope of higher education. Besides, the factors of situational, demographic, and socio-cultural have been revealed by a lot of previous studies. However, there has been not revealed clearly about empirical evidence on how the factors of situational and psychological can potentially affect the academic dishonesty while online exams happen to be without monitored by lecturers. Furthermore, this present study involved 237 accounting students of a state university. This present study aimed to find out how the aspects of pressure, opportunity, rationalization, competence, arrogance, and test anxiety affect the academics dishonesty. This research using quantitative explanative approach and also applied the method of data analysis by using multiple linear regression. Henceforth, it was found out that the factors of pressure, rationalization, and competence affect the academic dishonesty of accounting students positively and significantly. Regardless, this significant results could not be found in the factors of opportunity, arrogance, and test anxiety. Eventually, the findings indicated that either the institution and the lecturers must have strict rules and penalty for the fraudsters. Additionally, the accounting students must also prioritize the principles of integrity, open-minded, and fairness.